Morphotektonische Entwicklung von Kontinenträndern - Eine Untersuchung am Beispiel Ostaustraliens - Kubiniok, Jochen; Löffler, Ernst (ERDKUNDE, 1989)
Contrary to previous opinion, which considered the geomorphological development and in particular the uplift of the Eastern Australian Highlands as a relatively recent event (Kosciusko Uplift), new research indicates that the geomorphological history of the highlands dates back at least into the Cretaceous period. A review of the modern literature and the authors’ own research show that the present landscape developed from a Mesozoic erosion surface of low relief through uplift of the continental margin. The Great Escarpment was formed by uplift of the continental margin and headward erosion. Variations in the morphology of the Great Escarpment and the old land surfaces are the result of differential uplift of the continental margin, which commenced in the upper Cretaceous in connection with the plate tectonic movement of the Australian continent and the final break up of Gondwana. The rate of uplift decreases from south to north and the age of uplift becomes progressively younger in the same direction.